Manajemen Risiko Pemasangan Wifi pada Perusahaan Telekomunikasi dengan Framework Risk Information Technology - Loudry Palmarums Mustamu; Mewati Ayub; Swat Lie Liliawati (Jurnal Teknik Informatika dan Sistem Informasi, 2022)
In this research, an analysis of Wi-Fi products was carried out using Risk Framework, Information Technology (IT) Domain Risk Response, and decision tree method to determine decision making at the Telecommunication companies which occurs from January to September 2021. The Wi-Fi installation process was carried out to assess how far Telecommunication company had responded to problems related to IT risks. This analysis is carried out to help the Telecommunication company create a framework to respond to IT risks that have occurred, such as human risk errors, system disturbances, interference fromoutside parties, inventory control, as well as responding to problems related to IT risks such as problems related to possible risks to the system used. The goal is to provide recommendations to the company in accordance with the IT Risk Framework. Thedata sources are derived from a direct interview with the manager of the Telecommunication company and customer service data. The analysis refers to the process of installing Wi-Fi for the customers. Customer service data is analyzed using the Decision Tree in Weka. The results of the analysis are expected to support the Telecommunication company to be better inresponding and reacting to IT risk and incidents that have occurred, those that may occur at telecommunication installation.